2015
DOI: 10.1089/apc.2015.0063
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Decision-Making Among Kenyan HIV-Serodiscordant Couples Who Recently Conceived: Implications for Safer Conception Planning

Abstract: HIV-serodiscordant couples often choose to attempt pregnancy despite their HIV transmission risk. Optimizing delivery of HIV risk reduction strategies during peri-conception periods (i.e., safer conception) requires understanding how HIV-serodiscordant couples approach fertility decisions. We conducted 36 in-depth individual interviews with male and female partners of Kenyan heterosexual HIV-serodiscordant couples who recently conceived. Transcripts were analyzed by gender and HIV serostatus using open coding.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 46 publications
3
42
0
Order By: Relevance
“…The review found that SCS were largely unavailable in sub-Saharan Africa outside of research settings, except for general availability (i.e., not for safer conception specifically) of ART and VMMC. Availability of SCS methods was greatest in public health facilities providing general services for people living with HIV [2026, 31, 36, 3944, 4750, 56, 58, 59, 62, 63, 6668]. More advanced or expensive strategies such as sperm washing, or PrEP remain unavailable in most public health facilities due to cost and lack of provider training [1417, 23].…”
Section: Discussionmentioning
confidence: 99%
“…The review found that SCS were largely unavailable in sub-Saharan Africa outside of research settings, except for general availability (i.e., not for safer conception specifically) of ART and VMMC. Availability of SCS methods was greatest in public health facilities providing general services for people living with HIV [2026, 31, 36, 3944, 4750, 56, 58, 59, 62, 63, 6668]. More advanced or expensive strategies such as sperm washing, or PrEP remain unavailable in most public health facilities due to cost and lack of provider training [1417, 23].…”
Section: Discussionmentioning
confidence: 99%
“…T. Montgomery et al, 2012). Findings from the parent study cohort, published elsewhere (Ngure et al, 2014), reveal a similar dynamic in childbearing decisions; when men wanted a child but their wives did not, they used language such as “she must” and “I will force her.” Such intense divisions of power have been known to result in domestic violence against women (Pintye et al, 2015; Wingood & DiClemente, 2000), and HIV seropositive women are at higher risk of such abuse than their seronegative peers in both Kenya (Fonck et al, 2005; Onsomu et al, 2014) and Uganda (Emusu et al, 2009; Were et al, 2011). These patterns provide a possible explanation for why the seropositive men in this study were vocal about their control of household decisions and silent about the potential for taking PrEP to be burdensome to their spouses: they may experience their HIV diagnosis as a loss of masculine control, which they are subsequently attempting to re-establish in their homes.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical guidelines, including those from World Health Organization (2012), the American College of Obstetrics and Gynecologists (2014), and the US Panel on the Treatment of HIV Infected Pregnant Women and Prevention of Perinatal Transmission (2016), recommend PrEP as a safer conception strategy for individuals at high risk of HIV, and previous studies have demonstrated that couples affected by HIV welcome the opportunity to augment ART use with PrEP during pregnancy attempts. (Heffron, Mugo, et al, 2016; Matthews et al, 2014; Ngure et al, 2014; Ngure et al, 2016; Pintye et al, 2015; Seidman et al, 2016) Reported experience with PrEP was low among participants in our study with an HIV uninfected partner. Awareness of PrEP as a safer conception strategy was moderate among reproductive age participants with fertility desires and many identified potential barriers to HIV uninfected partners using PrEP during pregnancy attempts.…”
Section: Discussionmentioning
confidence: 62%
“…Effective management of HIV with antiretroviral therapy has enabled people living with HIV to achieve full life expectancy, including satisfying desires for pregnancy and family (Deeks, Lewin, & Havlir, 2013; Finocchario-Kessler et al, 2012; Massad et al, 2004; Mujugira et al, 2013; Oguntibeju, 2012; Pintye et al, 2015; Samji et al, 2013; Sharma et al, 2007). The preconception period, when couples intentionally forgo condoms to achieve pregnancy, can be accompanied by increased HIV transmission risk (Heffron, Pintye, Matthews, Weber, & Mugo, 2016), especially when viremia is not fully suppressed in the partner living with HIV.…”
Section: Introductionmentioning
confidence: 99%